The Implementation of Contextual Teaching and Learning (CTL) Model Based on Local Wisdom of Klambir Lima Kebun Village to Enhance Students' Critical Thinking Skills - Fadilah, Nina (The Future of Education Journal, 2025)
This research is motivated by the low critical thinking skills of students in mathematics learning, which is often perceived as abstract and irrelevant to everyday life. The purpose of this study is to describe the implementation of mathematics learning that integrates the social and local environmental context of Klambir Lima Kebun Village and to analyze its impact on improving students' critical thinking skills. The research method used is qualitative. The subjects of the study involve children at the elementary school level in Klambir Lima Kebun Village. The data collection instruments include tests of critical thinking skills, observation sheets of student activities, and documentation of local context involvement (such as plantation activities, social structure, or village economy). The results show that the integration of the local context of Klambir Lima Kebun Village makes the learning process more meaningful and stimulates students' curiosity. Students demonstrated significant improvement in critical thinking indicators, especially in aspects of problem analysis and decision-making based on real data. Thus, this local environment-based learning approach is effective in enhancing the quality of students' critical thinking while also fostering a love for the environment they live in.